Wacana Sejarah dalam Ungkapan Teater Betawi - Ninuk Klden-Probonegoro (LIPI Press, 1999)
The assumption which underlies this paper is that theater in general can document empirical events which take place in a society as the surroundings of the theater, and that such a documentation is put down and undergoes as sort of fixation in the narrative of that theater. Based on such an assumption the author tries to look into the narratives of the Betawi theaters, lenong,topen. In fact certain sorts of narrative deserve, according to the author, a special attention, since they migh document certain since they might document certain ideas whiche, though not manifaest in the performance, migh to be of great importance and significance.